The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1093/jas/skz337
|View full text |Cite
|
Sign up to set email alerts
|

Weaning age and post-weaning nursery feeding regime are important in improving the performance of lightweight pigs

Abstract: The aim was to investigate the effect of weaning age, weaning weight, and nursery feeding regime on post-weaning performance. The focus was on pigs weaned light, as they may be better off when weaned at a later age and/or offered a specialist nursery feeding regime. Piglets (n = 1,448) from one farrowing batch of 110 sows that farrowed over 2 wk were individually weighed and their morphometric measurements were taken at birth. Pigs were weaned on the same day, but variation in birth date resulted in variable w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Similarly, other authors have reported a greater lysine disappearance as a percentage of total intake at low energy intakes [ 23 ]. Consequently, most nutritional studies have focused on feeding high density diets, by increasing amino acid or energy concentrations during the nursery phase, as they considered that early interventions might be more effective [ 12 , 24 , 25 , 26 ]. However, other studies have also reported positive effects of dietary interventions during the grow-finishing phase [ 17 , 27 , 28 ], and others reported no advantage [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, other authors have reported a greater lysine disappearance as a percentage of total intake at low energy intakes [ 23 ]. Consequently, most nutritional studies have focused on feeding high density diets, by increasing amino acid or energy concentrations during the nursery phase, as they considered that early interventions might be more effective [ 12 , 24 , 25 , 26 ]. However, other studies have also reported positive effects of dietary interventions during the grow-finishing phase [ 17 , 27 , 28 ], and others reported no advantage [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Underdevelopment was marked by lighter GI organs and accessory organ weights, as well as lower specific maltase, glucoamylose, and pancreatic enzyme activity. Similarly, when pigs were divided into young (<32.4 wean age) versus old (>35.9 wean age) groups at a common wean date, higher mortality rates were observed in young (9.1%) compared to old pigs (5.0%; Huting et al, 2019 ). However, when divided into light verses heavy groups, no statistical differences were detected.…”
Section: Preweaning Strategies To Increase Feed Intake After Weaningmentioning
confidence: 99%
“…Considering the relevance of the specific classes of weight of the piglets at a given age was a first step in this direction. Delaying the weaning age by one week to an average of 32 days benefitted the performance of lighter pigs when reared to a common final weight (20 and 60 kg) [95]. Pigs weaned later, whatever the weight class, also had reduced mortality.…”
Section: Age and Live Weight At Weaningmentioning
confidence: 99%
“…However, there is the need for defining the target profiles of the ideal mature GIT microbiota in order to optimize weaning age. Follow-up studies regarding pigs under both genetic selection and standard rearing have indicated that the presence of bacteria capable of degrading complex carbohydrates, including fiber degrading organisms, is the hallmark of a mature microbiota in the colon or feces (growing-finishing pigs), including the Prevotella and Treponema genera [95][96][97][98][99]. Furthermore, the operational taxonomic units (OTUs) assigned to the Prevotella genus were genetically associated with growth performance during different growing phases [100].…”
Section: Age and Live Weight At Weaningmentioning
confidence: 99%